Rural Bamboo Trade in Kerala and Retail Markets - Krishnankutty, C. N. (Indian Forester, 2001)
Kerala rural Bamboo markets (Bamboo extracted from home-gardens is referred to as rural Bamboo) are dominated by a few private wholesale Bamboo depots in Palakkad District and is largely geared to meeting the demand from the neighbouring States. The survey of rural Bamhoo trade during the year 1994 in Kerala State, India, reveals that the major retail markets for Kerala rural Bamhoo are the consumption centres in the State of Tamil Nadu. During the year 1993-94, nearly 39% of rural Bamboo was sold to retail depots there, while 27% was brought directly by farmers for using as supports for banana (crops in Tamil Nadu. The trade to Karnataka State was 20%, while only 14% was consumed within Kerala. The Bamboo trade to Tamil Nadu has been declining due to shortage of supply. The real price of rural Bamboo has risen consistently and supply shortage, due to depletion of growing stock in home-gardens, seems to be the main reason behind the price increase. It is suggested to improve the growing stock of Bamboo in home-gardens through better management. The study also identifies the strength and vitality of Bamboo depots in the development of rural Bamboo resources.